KONDISI SOSIAL EKONOMI DAN NILAI TUKAR NELAYAN (NTN) AWAK KAPAL PURSE SEINE DI PELABUHAN BENOA, BALI - Anita Yolanda Purba; I Wayan Restu; Endang Wulandari Suryaningtyas; I Ketut Wija Negara (CV. ADIBA AISHA AMIRA, 2025)
Purse seine crew members play a strategic role in the success of fishing operations. Skills, experience, and effective coordination directly contribute to the quantity and quality of the catch. Vessel productivity is determined not only by technology and specifications, but also by the socioeconomic conditions of the crew, which are influenced by seasonal factors, profit-sharing systems, and fluctuations in fish prices. These conditions impact income stability, particularly for crew members (ABK), who generally do not receive a fixed salary. This study aims to analyze the socioeconomic conditions and welfare levels of purse seine crew members at Benoa Fishing Port, Bali, based on the fishermen’s Exchange Rate (Nilai Tukar Nelayan/NTN). This study applied a descriptive method with both quantitative and qualitative approaches through interviews and questionnaires, referring to 10 socioeconomic indicators from the BPS, including income, expenditure, home ownership, housing conditions, family health, access to healthcare, family education, access to transportation, security, and social access. The results show differences in welfare levels between caPTains and crew members. These differences indicate significant disparities in income, economic stability, and access to basic necessities. The findings are expected to serve as a reference for stakeholders in formulating policies to improve the welfare of purse seine crew members at Benoa Fishing Port and contribute to scientific knowledge.